PERANCANGAN DAN PEMBANGUNAN SISTEM PENILAIAN SISWA SD ERENOS - Vincent (STORAGE: Jurnal Ilmiah Teknik dan Ilmu Komputer, 2024)
Information systems include networks and internet technology which are an important part of organizational life, one of which is in the world of education. School education must be able to facilitate services for students. Currently there are more and more students studying at Erenos Elementary School. The assessment currently carried out at Erenos Elementary School is manual, namely using Microsoft Excel and producing report cards via Microsoft Word. This manual method can hinder the speed of teacher performance in student assessment and errors can also occur in recording and calculating, so this research aims to create a system that helps teachers in calculating the report card grades of Erenos Elementary School students so that it can be done more quickly and accurately. and accurate. The analysis and design method used in this research is UML (Unified Modeling Language). The results of this research show that a web-based information system can help teachers input student grade data precisely and accurately so as to produce e-reports quickly and accurately. In addition, web-based information systems can produce databases that can be used to analyze student progress and other information.